2014
DOI: 10.1002/rcm.6880
|View full text |Cite
|
Sign up to set email alerts
|

UV-visible degradation of boscalid - structural characterization of photoproducts and potential toxicity usingin silicotests

Abstract: With one exception, the structures proposed for the photoproducts on the basis of mass spectra interpretation have not been reported in previous studies. In silico toxicity predictions showed that two photoproducts are potentially more toxic than the parent compound considering oral rat LD50 while five photoproducts may induce mutagenic toxicity. With the exception of one compound, all photoproducts may potentially induce developmental toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Nevertheless, some of the described photoproducts can be found in environmental samples, e.g. boscalid photoproducts were found on grape leaves treated under field conditions . The present work focuses on the phototransformation of fludioxonil in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some of the described photoproducts can be found in environmental samples, e.g. boscalid photoproducts were found on grape leaves treated under field conditions . The present work focuses on the phototransformation of fludioxonil in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…boscalid photoproducts were found on grape leaves treated under field conditions. [17] The present work focuses on the phototransformation of fludioxonil in aqueous solution. Fludioxonil was introduced by Ciba-Geigy in 1990 to be primarily used as a foliar fungicide in order to control Botrytis cinerea, Monilinia, Sclerotinia, Rhizoctonia and Alternaria.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponded to ~88% and up to 100% degradation on glass and apple skin, respectively. Lassalle et al (2014) have previously observed that UV irradiation effectively degrades boscalid residues using a high-pressure mercury lamp irradiating 120 mL quartz tubes in a sonicator at 25 ± 3□C. While the UV dose to samples was not reported, 150 min of exposure of a 5 mg/L aqueous solution of boscalid to a lamp with a radiation flux of 6200 lumens (wavelength 200 to 650 nm) resulted in a 90% decrease in residues.…”
Section: Resultsmentioning
confidence: 99%
“…Using these wash techniques can increase the risk of microbial contamination (CDC, 1989; DiCaprio et al, 2015; Franz et al, 2008; Gombas, 2017). A potential alternative is the use of advanced oxidative processes (AOPs), for example the combinations of multiple treatments such as UV light, hydrogen peroxide, ozone, titanium dioxide and others that are capable of generating hydroxyl or other highly reactive radicals that can degrade pesticide residues (Junges et al, 2013; Lassalle et al, 2014; 2015; Manassero et al, 2010). AOP has been a common technique to degrade pollutants in wastewater for decades and has recently seen some application in the treatment of food commodities for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The first strategy consisted in establishing a list of boscalid metabolites previously identified in the literature in different media or organisms such as rats (Grosshans and Knoell, 2001) or soil (US EPA, 2003). We also included transformation products from electrochemical, photolytic or photocatalytic reactions (Lohmann et al, 2009;Lagunas-Allu e et al, 2010;Lassalle et al, 2014). The exact mass of each potential metabolite was calculated as well as several adducts, namely [MþH] þ , [MþNa] þ and [MþNH 4 ] þ .…”
Section: Analytical Strategy To Detect and Identify The Metabolitesmentioning
confidence: 99%